2016
DOI: 10.1371/journal.pone.0156635
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of SIgA and IgG Antibody-Secreting Cells in the Small Intestine of Bactrian Camels (Camelus bactrianus) of Different Ages

Abstract: Secretory immunoglobulin A (SIgA) and immunoglobulin G (IgG) antibody-secreting cells (ASCs) are two important cell types in the mucosal immune system. This study aimed to explore the distribution of these ASC populations in the small intestine of Bactrian camels of different ages. Twenty-four Alashan Bactrian camels were divided into the following four age groups: young (1–2 years), pubertal (3–5 years), middle-aged (6–16 years) and old (17–20 years). SIgA and IgG ASCs in the intestinal mucosa lamina propria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
3
12
0
Order By: Relevance
“…Mucosal immunoglobulins contribute to the immune homeostasis at the mucosal interface ( 216 ). The distribution of secretory IgA (SIgA) and IgG-secreting cells (ISCs) in the lamina propria of the small intestine of Bactrian camels suggests their significant contribution to mucosal immunity in this species ( 210 , 217 ). Similar to the age-related changes in the number of PP in the intestine of Bactrian camels, SIgA and IgG ISC numbers increase with age with a peak at puberty ( 210 , 217 ).…”
Section: Mucosal Immunity In Camelsmentioning
confidence: 99%
“…Mucosal immunoglobulins contribute to the immune homeostasis at the mucosal interface ( 216 ). The distribution of secretory IgA (SIgA) and IgG-secreting cells (ISCs) in the lamina propria of the small intestine of Bactrian camels suggests their significant contribution to mucosal immunity in this species ( 210 , 217 ). Similar to the age-related changes in the number of PP in the intestine of Bactrian camels, SIgA and IgG ISC numbers increase with age with a peak at puberty ( 210 , 217 ).…”
Section: Mucosal Immunity In Camelsmentioning
confidence: 99%
“…When IgA‐mediated mucosal elimination of antigens is unsuccessful, such as when the first‐line immunologic barrier is destroyed, IgG, with its proinflammatory activity, can rapidly recruit phagocytic innate immune cells through the activation of an inflammatory reaction, helping to eliminate invading pathogens (Sylvestre & Ravetch, ; Ogra, ; Cerutti, et al, ). In recent years, the expression and distribution characteristics of IgA and IgG were mainly reported in the palatine and pharyngeal tonsils of cattle ( Bos taurus ) (Manesse et al, ; Yasuda, et al, ), the pharyngeal tonsils of human ( Homo sapiens; Ishikawa, Wicher, & Arbesman, ; Boyaka et al, ), the respiratory tract of pig (Li, Liu, Gao, Yu, & Yang, ), and the palatine tonsil and small intestine of the Bactrian camel (Jia et al, ; Zhang, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, bovine CDR3 is known for its ultralong subset, which ranges from 50 to 60 amino acids [44]. [46]. It has been clearly indicated that aging has a significant impact on the density and distribution of IgA + and IgG + cells [45].…”
Section: The Hcabsmentioning
confidence: 99%
“…The scattered distribution of the IgG and IgA ASCs in the small intestine is of significant importance for providing full-protection and immune surveillance of the mucosal immune homeostasis and intestinal integrity [45] [46]. The densities of IgA ASCs are great-er than IgG ASCs in the duodenum, jejunum and ileum of young and pubertal camels [46].…”
Section: The Tissuementioning
confidence: 99%
See 1 more Smart Citation